Peanut ball use for reducing maternal fatigue during labor: protocol for a randomized clinical trial (Research, Society and Development, 2022)
Objectives: Develop a protocol of the use of the Peanut Ball (PB) to evaluate its effectiveness compared to usual care on decreasing maternal fatigue during labor. Methods: This is the development of a randomized clinical trial protocol. Perform an intervention group or use the Peanut Ball through five postures, according to an obstetric assessment. To assess maternal fatigue, the Maternal Perception of Childbirth Fatigue Questionnaire (MCFQ) will be used in the form of an interview. Results: The proposed protocol is according to the evolution of labor: height and positioning of the fetal presentation, erasure and uterine dilation and the presence of early blood flow. Postures with fetal presentation in the upper strait: postures with abduction and external rotation hips will be encouraged using PB. Posture according to the fetal position in the upper strait: posture that cancels gravity will be encouraged: lateral decubitus posture with PB between legs. If the parturient feels like pushing or pushing down with the baby tall and cervix before 8-10 centimeters of uterine dilation, posture that nullifies gravity will be encouraged: lateral decubitus with the aid of the ball, with the hips in abduction and external rotation Conclusion: A specific protocol was developed with the use of Peanut Ball, through an obstetric evaluation, to reduce maternal fatigue during labor.